Upaya Meningkatkan Aktivitas dan Hasil Belajar Akidah Akhlak Melalui Model Pembelajaran STAD - Sulaiman, Akhmad (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2023)
The low learning value of the Akidah Akhlak subject is what inspired this study. Through the STAD learning paradigm, the study seeks to improve the activity levels and academic results of Class XII MIA MAN Purwakarta students in semester I of the 2022/2023 academic year. A two-cycle class behavior survey was the methodology used in this study. There are always two sessions in a cycle. Every cycle includes planning, implementing, observing, and reflecting phases. Research data is gathered through written tests and observation. According to the research findings, the pre-test completion rate for students was 40.30%, with a 59.15 class average. In Cycle I, the proportion of learning outcomes that were fully attained rose to 65.30% on average.